Evaluation of learning during the COVID-19 pandemic - Fitriani Sabila; Naureza Rania Shafa; Nisrina Kurnia Maharani; Sadam Mochammad Rashad; Theitsar Syakhisksar Rohim Permana; Lien Halimah (Curricula: Journal of Curriculum Development, 2023)
The learning process is an essential part of education, as it aims to equip students with experiential abilities, moral understanding, and skills, enabling positive developments in their learning journey. Success in the learning process serves as a benchmark for achieving learning goals. An evaluation or assessment process is necessary to determine the achievement of learning objectives. Evaluation in learning holds significant strategic meaning in education. Learning evaluation aims to assess the development of students' learning outcomes after participating in the learning process. Evaluation is also conducted to determine the effectiveness and efficiency of the methods employed by the teacher during the learning process. The research method used in this study is qualitative research with a descriptive content analysis approach. The critical role of learning evaluation is not only defined by the system and characteristics of educators but also by the objectives, functions, principles, validity, and reliability of the evaluation tools used, which can influence the evaluation process in learning.